Upaya Mewujudkan Masyarakat Bermartabat di Desa Batu Gingging, Kec. Bangun Purba, Kab. Deli Serdang - Cahaya Permata; Amanda Putri Ramadhani; Andini Syafitri; Nuraina Nabilah; Risa Nur Fadhillah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Regular KKN Group of 27 North Sumatra State Islamic University in Batu Gingging Village, Kec. Bangun Purba, Kab. Deli Medium is a form of experience in the Tri Dharma of Higher Education, namely Devotion. The Real Work Lecture (KKN) at the State Islamic University of North Sumatra was held on 18 July-18 August 2022 with the theme